Immune-mediated comorbidities in Saudi patients with narcolepsy - Alomar, Majed (Nat Sci Sleep, 2019)
Background: Autoimmunity has been proposed as a cause of narcolepsy. A few studies have assessed comorbid autoimmune diseases in patients with narcolepsy, with conflicting results; however, no study has assessed autoimmune diseases in Arab narcolepsy patients. This study aimed to assess the coexistence of immune-mediated conditions such as allergies, autoimmune diseases, and autoinflammatory diseases in patients with narcolepsy type 1 (with cataplexy) (NT1) and narcolepsy type 2 (without cataplexy) (NT2). Methods: Personal and family history of autoimmune/autoinflammatory and allergic disorders was collected using a questionnaire in 80 consecutive Saudi patients with narcolepsy (46 NT1 and 24 NT2), who were diagnosed according to the International Classification of Sleep Disorders, Third Edition. The control group comprised 222 adults from the general population. Results: Comorbid autoimmune/autoinflammatory diseases were reported by 21.4% of the NT1 patients, and 12.2% of the controls, with no significant difference between cases and controls in a model adjusted for confounding covariates. However, allergic disorders were significantly more prevalent among NT1 patients. Both comorbid autoimmune/autoinflammatory and allergic disorders were significantly more prevalent among NT2 patients compared to controls. No differences in demographic and clinical characteristics were detected between narcolepsy patients with and without autoimmune/autoinflammatory diseases. Conclusion: NT1 is not associated with increased comorbid autoimmune diseases in the studied sample of Saudi patients. However, autoimmune diseases are associated with NT2, and allergic disorders are associated with both NT1 and NT2. These findings suggest the existence of dysregulation in the immune system of narcolepsy patients that requires further research.